Entrepreneurial intention of students: The role of digital tools and personal factors in entrepreneurship education - Aivars Spilbergs; Inese Mavlutova; Kristaps Lesinskis (PLoS ONE, 2026)
Education is changing due to digital transformation, which is especially significant for entrepreneurship since students’ readiness to start their own businesses may be assessed by their proficiency with digital technologies. An experimental group educated with the AI-based digital tool KABADA, and a control group trained through traditional workshops in a quasi-experiment with 819 students from Southern and Central-Eastern Europe were compared to examine this relationship. The effects of gender, education, past entrepreneurial experience, self-evaluation, and motivation on entrepreneurial intention were tested using ordinal logistic regression. Compared to traditional workshops, the results demonstrate that digital tools significantly increase students’ entrepreneurial intention; the best indicators were self-assessment and entrepreneurial desire. While education level had no discernible impact, gender and previous entrepreneurship experience were also important factors. The findings show that one of the most effective ways to encourage entrepreneurial purpose is to incorporate digital tools into entrepreneurship education. This study emphasizes the importance of students acquiring digital skills in order to increase their preparedness for entrepreneurship in technology-driven economies.